Addressing insurance‐related barriers to novel antiobesity medications: Lessons to be learned from bariatric surgery. Issue 12 (3rd October 2022) - Gasoyan, Hamlet; Sarwer, David B.
Abstract: The past decade has witnessed significant progress in the development of new antiobesity medications, with several having greater efficacy than pharmacological agents previously approved by the Food and Drug Administration (FDA). Despite the potential of new medications to combat America's obesity crisis, access to these agents is severely limited. This Perspective presents the current coverage landscape for antiobesity medications, including the recent requirement by the US Office of Personnel Management for Federal Employees Health Benefits Program carriers to offer adequate coverage of FDA‐approved antiobesity medications, and it makes parallels with conditions that made expanded insurance coverage for bariatric surgery possible, as well as emphasizes the need for additional action by the legislature and the Centers for Medicare and Medicaid Services to expand coverage of evidence‐based obesity treatments.